Increased circulating myeloid-derived suppressor cells in vivax malaria and severe falciparum malaria - Leo Leonardo; Enny Kenangalem; Jeanne R. Poespoprodjo; Rintis Noviyanti; Ric N. Price; Nicholas M. Anstey; Gabriela Minigo; Steven Kho (Malaria Journal, 2022)
Abstract Background Circulating myeloid-derived-suppressor-cells (MDSC) with immunosuppressive function are increased in human experimental Plasmodium falciparum infection, but have not been studied in clinical malaria. Methods Using flow-cytometry, circulating polymorphonuclear-MDSC were evaluated in cryopreserved samples from patients with uncomplicated Plasmodium vivax (n = 8) and uncomplicated (n = 4) and severe (n = 16) falciparum malaria from Papua, Indonesia. Results The absolute number of circulating polymorphonuclear-MDSC were significantly elevated in severe falciparum malaria patients compared to controls (n = 10). Polymorphonuclear-MDSC levels in uncomplicated vivax malaria were also elevated to levels comparable to that seen in severe falciparum malaria. Conclusion Control of expansion of immunosuppressive MDSC may be important for development of effective immune responses in falciparum and vivax malaria.